Acute Improvement of Vertical Jump Performance After Isometric Squats Depends on Knee Angle and Vertical Jumping Ability. - Tsoukos, Athanasios; Bogdanis, Gregory C; Terzis, Gerasimos; Veligekas, Panagiotis (J Strength Cond Res, 2016)
Tsoukos, A, Bogdanis, GC, Terzis, G, and Veligekas, P. Acute improvement of vertical jump performance after isometric squats depends on knee angle and vertical jumping ability. J Strength Cond Res 30(8): 2250-2257, 2016-This study examined the acute effects of maximum isometric squats at 2 different knee angles (90 or 140°) on countermovement jump (CMJ) performance in power athletes. Fourteen national-level male track and field power athletes completed 3 main trials (2 experimental and 1 control) in a randomized and counterbalanced order 1 week apart. Countermovement jump performance was evaluated using a force-plate before and 15 seconds, 3, 6, 9, and 12 minutes after 3 sets of 3 seconds maximum isometric contractions with 1-minute rest in between, from a squat position with knee angle set at 90 or 140°. Countermovement jump performance was improved compared with baseline only in the 140° condition by 3.8 ± 1.2% on the 12th minute of recovery (p = 0.027), whereas there was no change in CMJ height in the 90° condition. In the control condition, there was a decrease in CMJ performance over time, reaching -3.6 ± 1.2% (p = 0.049) after 12 minutes of recovery. To determine the possible effects of baseline jump performance on subsequent CMJ performance, subjects were divided into 2 groups ("high jumpers" and "low jumpers"). The baseline CMJ values of "high jumpers" and "low jumpers" differed significantly (CMJ: 45.1 ± 2.2 vs. 37.1 ± 3.9 cm, respectively, p = 0.001). Countermovement jump was increased only in the "high jumpers" group by 5.4 ± 1.4% (p = 0.001) and 7.4 ± 1.2% (p = 0.001) at the knee angles of 90 and 140°, respectively. This improvement was larger at the 140° angle (p = 0.049). Knee angle during isometric squats and vertical jumping ability are important determinants of the acute CMJ performance increase observed after a conditioning activity.
Keywords: Adult; Athletes; Athletic Performance; Exercise; Humans; Isometric Contraction; Knee Joint; Male; muscle fatigue; Track and field; Young Adult